The Scientific Dating of Standing Buildings. (November 2017) - Alcock, Nathaniel W.
The techniques of dendrochronology (tree-ring dating) and radiocarbon ( 14 C) dating are described, as they are applied to historic buildings. Both rely on determining the felling dates of the trees used in their construction. For dendrochronology, the construction of master chronologies and the matching of individual ring-width sequences to them is described and, for radiocarbon dating, the use of tree-ring results in calibration. Results of dating are discussed, ranging from the cathedrals of Peterborough and Beauvais and the development of crown-post roof structures, to the dating and identification of standing medieval peasant houses, particularly those built using cruck construction.